Mitos Vagina Ideal dalam Iklan Sabun Kewanitaan - Wiwid Adiyanto (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2021)
Feminine soap is promoted as a healthy product and has a positive impact on household life, including Purbasari Manjakani Whitening. On the other hand, medical research has shown potential health risks from using vaginal cleansing products. Relatively affordable prices and simulated impacts have made Purbasari indulge in the whitening of the top 5 main products for the past 4 years. The purpose of this study was to dissect the myths related to the vagina from the advertisement of Purbasari Manjakani Whitening. This study uses qualitative descriptive approach with semiology analysis of Roland Barthes. The results of this study indicate that the ideal vagina is one that is tight, white, and fragrant. Myths naturalized thus establishing a panoptic effect for women to keep their vaginas in the submissive body category. Biopower works through family harmony issues. This condition traps women on an endless idealistic journey to fulfill vaginal instructions. The ideal vaginal construction cannot be separated from the power relation in which sexual relations are no longer the satisfaction of both parties, flowing to men as husbands.